Forming method of integrated metal structural part and integrated metal structural part

By using stainless steel 316L powder and aluminum oxide nanopowder on the operating panel, and forming a self-healing coating of silver nanoparticles on the surface, the problem of insufficient wear resistance and corrosion resistance of the operating panel is solved. , achieving higher wear and corrosion resistance, extending service life and reducing maintenance costs.

CN119237742APending Publication Date: 2025-01-03SUZHOU SHUOFENG PRECISION MACHINERY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411296747.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The operation panel has poor wear resistance and corrosion resistance after long-term use, resulting in reduced protection performance and wear problems.

Method used

Nano-metal ceramic composite material is prepared by stainless steel 316L powder and aluminum oxide nanopowder. The operation panel is prepared by injection molding, and a silver nanoparticle self-healing coating is formed on its surface. The electrophoretic deposition method is used to form a wear-resistant and corrosion-resistant surface. Protective layer.

Benefits of technology

It significantly improves the wear and corrosion resistance of the operating panel, extends the service life, reduces maintenance needs, and enhances the usability and durability of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237742A_ABST
    Figure CN119237742A_ABST
Patent Text Reader

Abstract

The invention discloses a forming method of an integrated metal structural part and the integrated metal structural part. The forming method comprises the following steps that firstly, stainless steel 316L powder is selected as metal powder, and aluminum oxide nano powder is selected as ceramic nano powder; 2, injecting the slurry into a preheated mold, and after injection is completed, keeping the pressure in the mold for 5-10 seconds to ensure that the slurry fully fills the mold and is cured; thirdly, the injection-molded product is subjected to heat treatment, and the surface of the taken-out operation panel is in a rough state; 4, preparing a silver nanoparticle self-repairing coating; 5, depositing the nano-particles on the surface of the nano-metal ceramic composite material to form a coating by adopting an electrophoretic deposition method and utilizing the action of an electric field; sixthly, the self-repairing coating is subjected to curing treatment; and seventhly, the cured coating is ground and polished. The problem that the operation panel is poor in abrasion resistance and corrosion resistance after being used for a long time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal structural part production, in particular to a forming method of an integrated metal structural part and the integrated metal structural part. Background Art

[0002] As the core control interface of equipment and machines, the operation panel has many characteristics and a wide range of applications. The operation panel is mostly made of metal materials such as steel and aluminum alloy. These materials are lightweight, high-strength, fire-resistant, corrosion-resistant and durable. The design of the operation panel focuses on ergonomics. The buttons, knobs, display screens and other components are reasonably laid out for easy use by operators. The metal structural parts have high strength and rigidity and can withstand certain impacts and vibrations to ensure the stability and durability of the operation panel. Generally, a stamping process is used to place the metal material under a press through a mold and apply pressure to cause it to undergo plastic deformation, thereby obtaining the desired shape and size.

[0003] For example, the Chinese authorized patent "Forming method of integrated metal structure and integrated metal structure" with announcement number CN104010463A, the forming method of integrated metal structure includes the steps of: providing a main metal material and processing it into a metal main structure; providing a component metal material and processing it into a metal secondary structure component; fixing the metal main structure and the metal secondary structure component together to form an integrated metal structure of the electronic device by a low-temperature metal bonding method, and the temperature rise of the bonded metal part during the implementation of the low-temperature metal bonding method is less than 300°C. The forming method and the integrated metal shell and middle frame plate of the electronic device produced by the forming method.

[0004] Although the above-mentioned existing technology can be applied to the production of metal operating panels, the surface of the operating panel is prone to corrosion due to the influence of the use environment factors, which accelerates aging and reduces the protection performance. At the same time, the operating panel is prone to wear due to long-term pressing of keys and continuous friction contact of buttons and human touch. Therefore, it does not meet the existing needs. In this regard, we propose a molding method of integrated metal structural parts and an integrated metal structural part. Summary of the invention

[0005] The object of the present invention is to provide a forming method of an integrated metal structure and an integrated metal structure to solve the problem of poor wear resistance and corrosion resistance of the operating panel after long-term use mentioned in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a forming method of an integrated metal structural part and an integrated metal structural part, comprising the following steps: Step 1: Select stainless steel 316L powder as metal powder and alumina nano powder as ceramic nano powder, and use the two to prepare nano metal ceramic composite material slurry; Step 2: Inject the slurry into the preheated mold and turn on the mold cooling system. After the injection is completed, maintain the pressure in the mold for 5-10 seconds to ensure that the slurry fully fills the mold and solidifies. Gradually release the pressure and open the mold to take out the parts after cooling to room temperature. Step 3: heat-treat the injection-molded product to remove the binder and enhance the material performance. The surface of the operation panel after removal is rough; Step 4: preparing a silver nanoparticle self-repairing coating; Step 5: using an electrophoretic deposition method to deposit nanoparticles on the surface of the nano-metal-ceramic composite material using an electric field to form a coating; Step 6: Curing the self-repairing coating to make the coating closely bonded to the substrate and achieve the required mechanical properties and self-repairing properties; Step 7: Grind and polish the cured coating to obtain a wear-resistant and corrosion-resistant operating panel product.

[0007] Preferably, the preparation of the nano-metal ceramic composite material slurry comprises the following steps: Step 1: Use a silane coupling agent to modify the surface of the aluminum oxide nanopowder. The modification time is 2 hours and the modification temperature is 60°C. After modification, remove the excess coupling agent by centrifugal washing to ensure that the powder surface is clean and free of residue; Step 2: Mix the modified alumina nanopowder and stainless steel powder in a predetermined ratio, add a dispersant and a solvent to form a slurry; Step 3: Use an ultrasonic processor to mechanically stir the slurry during the ultrasonic treatment process, use a pH meter to monitor the pH value of the slurry in real time, and adjust the pH value to a range of 8-9 by automatically dropping a dilute acid or dilute alkali solution; Step 4: After the ultrasonic and mechanical stirring are completed, a predetermined amount of dispersant is added and stirring is continued for 30 minutes to allow the polymer dispersant to be fully adsorbed on the surface of the nanoparticles to form a stable dispersion system; Step 5: Introduce the slurry into the microfluidic chip, use the laminar flow effect and shear force to further refine the dispersion of the nanoparticles, collect the evenly dispersed slurry at the microchannel outlet, filter the evenly dispersed slurry, and obtain a slurry product of the nano-metal-ceramic composite material.

[0008] Preferably, the preparation of the silver nanoparticle self-repairing coating comprises the following steps: Step 1: Select silver nanoparticles with self-repairing function; Step 2: Using silver nitrate as a precursor, reducing it in ethylene glycol to generate AgNPs, and adding polyvinyl pyrrolidone as a stabilizer; Step 3: The reaction temperature is controlled at 150°C, the reaction time is 2 hours, the molar ratio of polyvinyl pyrrolidone to silver nitrate is 1:1, and EG is used as a solvent and a reducing agent; Step 4: Disperse the nanoparticles in ethanol, add an appropriate amount of silane coupling agent, stir and react for 2 hours, and control the temperature at 60°C. After the reaction is completed, remove the excess coupling agent by centrifugal washing to ensure that the surface of the nanoparticles is clean and free of residue; Step 5: Add the modified self-healing nanoparticles to the epoxy resin base material in proportion, and use an ultrasonic processor to disperse the mixture. The ultrasonic frequency is 20 kHz, the power is 400 W, and the processing time is 30 minutes to ensure that the nanoparticles are evenly dispersed in the base material; Step 6: Adjust the viscosity of the slurry as needed, add diluent or thickener, and adjust it to a suitable range by dropping dilute acid or dilute alkali solution to obtain a self-repairing coating.

[0009] Preferably, the integrated metal structural part is the outer shell of the operating panel, the outer shell includes a plate body forming the main outline of the operating panel, the outer surface of the plate body is provided with a plurality of functional grooves, the functional grooves are correspondingly provided with a plurality of button reserved openings, and the plate body, functional grooves and button reserved openings are integrally injection molded.

[0010] Preferably, the surfaces of the plate body, the functional slots and the button reserved openings are all provided with a self-repairing coating.

[0011] Preferably, in the step 1, the particle size range of the stainless steel 316L powder is 10-30 μm, and the particle size range of the alumina nanopowder is 50-100 nm.

[0012] Preferably, the preheating temperature of the mold in step 2 is 80-100° C., the sintering temperature of the heat treatment in step 3 is 1200-1350° C., the curing temperature in step 6 is 150-200° C., and the curing time is 1-2 hours.

[0013] Preferably, the dispersant is polyethylene glycol PEG, the solvent is ethanol, the mass ratio of the dispersant to the total mass of the powder is 1:1.5, and the binder is polyvinyl alcohol PVA, which accounts for 2.5% of the total mass of the metal powder and the ceramic powder.

[0014] Preferably, the ultrasonic processor sets the ultrasonic frequency to 20 kHz, the power to 400 W, and the processing time to 30 minutes.

[0015] Preferably, the microchannel size of the microfluidic chip is 100 μm×100 μm, and the flow rate at the microchannel inlet is set to 0.5 mL / min.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention selects stainless steel 316L powder because it has excellent corrosion resistance, high temperature resistance and good mechanical properties. Alumina nanopowder has high hardness, wear resistance and chemical stability. Its nano effect is used to improve the overall performance of the composite material. Polyethylene glycol is used as a dispersant to effectively reduce the agglomeration between powders and promote the uniform dispersion of nanoparticles in metal powders. Ethanol is used as a solvent to provide good solubility and slurry fluidity. Polyvinyl alcohol can enhance the adhesion of the slurry and the strength of the material after molding.

[0017] 2. The present invention uses a silane coupling agent to modify the surface of aluminum oxide nanopowder, forms an organic film on the surface of the nanoparticles through chemical reaction, improves its compatibility with non-metallic substrates, and after modification, removes excess silane coupling agent through a centrifuge to ensure that the surface of the nanopowder is clean and free of residue, providing favorable conditions for subsequent mixing and dispersion. The slurry is introduced into a microfluidic chip, and the size effect and laminar flow effect of the microchannel are used in combination with shear force to further refine the dispersion of the nanoparticles and ensure the uniformity of the slurry. By controlling the flow rate at the microchannel inlet, the slurry can be accurately controlled and efficiently dispersed.

[0018] 3. The present invention adopts injection molding to accurately control the flow and filling process of the material, ensuring that the nano-metal ceramic composite material is evenly distributed in the mold, thereby obtaining high-precision products and being able to manufacture local structures with complex shapes and fine structures. The nano-metal ceramic composite material can be easily realized through injection molding to achieve design requirements that are difficult to achieve with traditional processing methods, such as thin walls, deep cavities, threads and other structures. During the injection molding process, the nanostructure of the nano-metal ceramic composite material can be effectively maintained, ensuring that it can still maintain excellent mechanical and physical properties after molding, such as high strength, high hardness, wear resistance and corrosion resistance.

[0019] 4. The present invention is provided with a self-repairing coating, which can automatically repair small cracks or scratches on the surface of the operating panel to prevent further damage, thereby significantly extending the service life of the operating panel. This feature reduces the need for replacement or repair due to surface damage. Through the automatic repair function, the self-repairing coating can maintain the integrity and smoothness of the surface of the operating panel, improve its ability to resist external mechanical stress and environmental erosion, thereby enhancing its durability. Since the self-repairing coating can automatically repair surface damage, the number of repairs due to surface damage is reduced, and maintenance costs are reduced. In some cases, the self-repairing coating can even be repaired without interrupting the use of the equipment, thereby simplifying the maintenance process and improving the availability of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1A perspective view of the present invention; Figure 2 It is a rear view of the present invention; Figure 3 It is a schematic diagram of the local structure of the present invention; Figure 4 The present invention is a flow chart for preparing the nano-metal ceramic composite material; Figure 5 The figure is a process flow chart of the operation panel forming process of the present invention.

[0021] In the figure: 1. Board body; 2. Function slot; 3. Key reserved opening; 4. Self-healing coating. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0023] See also Figure 1-5 The present invention provides an embodiment: a forming method of an integrated metal structure and an integrated metal structure, comprising the following steps: Step 1: Select stainless steel 316L powder as metal powder and alumina nano powder as ceramic nano powder, and use the two to prepare nano metal ceramic composite material slurry, the particle size range of stainless steel 316L powder is 10-30 μm, and the particle size range of alumina nano powder is 50-100 nm; Step 2: Inject the slurry into the preheated mold at 80-100°C, and turn on the mold cooling system. After the injection is completed, maintain the pressure in the mold for 5-10 seconds to ensure that the slurry fully fills the mold and solidifies. Gradually release the pressure, and open the mold to take out the parts after cooling to room temperature. Step 3: heat treat the injection molded product at a sintering temperature of 1200-1350°C to remove the binder to enhance the material performance. The surface of the operation panel after removal is rough; Step 4: preparing a silver nanoparticle self-repairing coating; Step 5: using an electrophoretic deposition method to deposit nanoparticles on the surface of the nano-metal-ceramic composite material using an electric field to form a coating; Step 6: Curing the self-repairing coating at a temperature of 150-200°C for 1-2 hours, so that the coating is closely bonded to the substrate and achieves the required mechanical properties and self-repairing properties; Step 7: Grind and polish the cured coating to obtain a wear-resistant and corrosion-resistant operating panel product.

[0024] By combining stainless steel 316L powder and alumina nanopowder, the prepared nano-metal ceramic composite material has excellent mechanical properties and corrosion resistance. Stainless steel 316L provides good strength and corrosion resistance, while alumina nanopowder significantly improves the hardness and wear resistance of the material, thereby improving the service life and performance of the operation panel as a whole. The injection molding process can ensure the one-piece molding of components such as the board body, function slots and button reservations, which not only improves production efficiency, but also ensures high precision and consistency of the product. In addition, the practice of preheating the mold and maintaining pressure after injection helps the slurry to fully fill the mold and reduce defects, further improving the quality of the product. The high-temperature sintering process removes the binder, significantly enhances the mechanical properties of the material, and makes its surface reach a certain degree of roughness, providing a good foundation for the subsequent adhesion of the coating. This treatment method helps to improve the overall stability and durability of the material See also Figure 5 The preparation of nano-metal ceramic composite material slurry includes the following steps: Step 1: Use a silane coupling agent to modify the surface of the aluminum oxide nanopowder. The modification time is 2 hours and the modification temperature is 60°C. After modification, remove the excess coupling agent by centrifugal washing to ensure that the powder surface is clean and free of residue; Step 2: Mix the modified alumina nanopowder and stainless steel powder in a predetermined ratio, add a dispersant and a solvent, wherein the dispersant is polyethylene glycol PEG, the solvent is ethanol, and the total mass ratio of the powder is 1:1.5, and the binder is polyvinyl alcohol PVA, which accounts for 2.5% of the total mass of the metal powder and the ceramic powder, to form a slurry; Step 3: Use an ultrasonic processor, set the ultrasonic frequency to 20kHz, the power to 400W, and the processing time to 30 minutes. During the ultrasonic treatment, the slurry is mechanically stirred, and the pH value of the slurry is monitored in real time with a pH meter, and the pH is adjusted to the range of 8-9 by automatically dropping a dilute acid or dilute alkali solution; Step 4: After the ultrasonic and mechanical stirring are completed, a predetermined amount of dispersant is added and stirring is continued for 30 minutes to allow the polymer dispersant to be fully adsorbed on the surface of the nanoparticles to form a stable dispersion system; Step 5: Introduce the slurry into a microfluidic chip with a microchannel size of 100 μm × 100 μm. Set the flow rate at the microchannel inlet to 0.5 mL / min. Use laminar flow effect and shear force to further refine the dispersion of the nanoparticles. Collect the evenly dispersed slurry at the microchannel outlet, filter the evenly dispersed slurry, and obtain a slurry product of a nano-metal-ceramic composite material.

[0025] The surface modification of alumina nanopowders using silane coupling agents effectively improves the surface properties of the nanoparticles, making them easier to disperse in solvents. This reduces the agglomeration of nanoparticles and improves the uniformity and stability of the slurry. By precisely controlling the ratio of stainless steel powder to alumina nanopowder and adding appropriate amounts of dispersants, solvents and binders, a slurry with ideal properties is formed. This optimization not only improves the mechanical properties of the material, but also ensures the fluidity and formability of the slurry during subsequent processing. The slurry is introduced into a microfluidic chip, and the dispersion of the nanoparticles is further refined using laminar flow effects and shear forces. This method can prepare nano-metal-ceramic composite slurries with higher dispersion and smaller particle size distribution, thereby improving the density and performance of the material.

[0026] The preparation of the silver nanoparticle self-healing coating includes the following steps: Step 1: Select silver nanoparticles with self-repairing function; Step 2: Using silver nitrate as a precursor, reducing it in ethylene glycol to generate AgNPs, and adding polyvinyl pyrrolidone as a stabilizer; Step 3: The reaction temperature is controlled at 150°C, the reaction time is 2 hours, the molar ratio of polyvinyl pyrrolidone to silver nitrate is 1:1, and EG is used as a solvent and a reducing agent; Step 4: Disperse the nanoparticles in ethanol, add an appropriate amount of silane coupling agent, stir and react for 2 hours, and control the temperature at 60°C. After the reaction is completed, remove the excess coupling agent by centrifugal washing to ensure that the surface of the nanoparticles is clean and free of residue; Step 5: Add the modified self-healing nanoparticles to the epoxy resin base material in proportion, and use an ultrasonic processor to disperse the mixture. The ultrasonic frequency is 20 kHz, the power is 400 W, and the processing time is 30 minutes to ensure that the nanoparticles are evenly dispersed in the base material; Step 6: Adjust the viscosity of the slurry as needed, add diluent or thickener, and adjust it to a suitable range by dropping dilute acid or dilute alkali solution to obtain a self-repairing coating.

[0027] Silver nanoparticles with self-healing properties were selected during the preparation process. This coating can self-repair and restore its original integrity and performance when it is slightly damaged. This property significantly extends the service life of the coating and reduces the frequency of maintenance and replacement. AgNPs are generated by reducing silver nitrate in ethylene glycol as a precursor, and polyvinyl pyrrolidone is added as a stabilizer to ensure the stability and uniform dispersion of the silver nanoparticles in the solution. This helps to form a uniform and dense coating during subsequent processing and improves the overall performance of the coating. The surface modification of the nanoparticles by silane coupling agents improves the compatibility between the nanoparticles and the epoxy resin base. The use of an ultrasonic processor ensures the uniform dispersion of the nanoparticles in the base, thereby improving the adhesion between the coating and the substrate. This tight bond helps prevent the coating from peeling or cracking during use.

[0028] See also Figure 2 , Figure 3 and Figure 4 The integrated metal structure is the shell of the operation panel. The shell includes a plate body 1 that forms the main outline of the operation panel. The outer surface of the plate body 1 is provided with a plurality of function slots 2. The function slots 2 are provided with a plurality of button reserved openings 3 corresponding to the function slots 2. The plate body 1, the function slots 2 and the button reserved openings 3 are integrally injection molded. The surfaces of the plate body 1, the function slots 2 and the button reserved openings 3 are all provided with a self-repairing coating 4. The integral injection molding process ensures a seamless connection between the plate body, the function slots and the button reserved openings, avoiding the seams and gaps that may be generated by the traditional multi-component assembly. This not only improves the overall aesthetics of the product, but also significantly enhances its structural strength, making the shell more durable, simplifying the production process, reducing the number of parts and assembly steps, thereby reducing production costs and cycles. In addition, the application of the self-repairing coating provides an additional protective layer for the operation panel shell because it reduces the possible errors and failure points during the assembly process, and also improves the production efficiency and yield rate of the product. When the surface of the shell is scratched, worn or slightly damaged, the self-repairing coating can automatically repair these damages to maintain the integrity and functionality of the shell. This feature significantly extends the service life of the product and reduces the need for replacement due to accidental damage. It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for forming an integrated metal structure, applied to an operation panel, characterized in that: The following steps are involved: Step 1: Select stainless steel 316L powder as metal powder and alumina nano powder as ceramic nano powder, and use the two to prepare nano metal ceramic composite material slurry; Step 2: Inject the slurry into the preheated mold and turn on the mold cooling system. After the injection is completed, maintain the pressure in the mold for 5-10 seconds to ensure that the slurry fully fills the mold and solidifies. Gradually release the pressure and open the mold to take out the parts after cooling to room temperature. Step 3: heat-treat the injection-molded product to remove the binder and enhance the material performance. The surface of the operation panel after removal is rough; Step 4: preparing a silver nanoparticle self-repairing coating; Step 5: using an electrophoretic deposition method to deposit nanoparticles on the surface of the nano-metal-ceramic composite material using an electric field to form a coating; Step 6: Curing the self-repairing coating to make the coating closely bonded to the substrate and achieve the required mechanical properties and self-repairing properties; Step 7: Grind and polish the cured coating to obtain a wear-resistant and corrosion-resistant operating panel product.

2. The method for forming an integrated metal structure according to claim 1, characterized in that: The preparation of the nano-metal ceramic composite material slurry comprises the following steps: Step 1: Use a silane coupling agent to modify the surface of the aluminum oxide nanopowder. The modification time is 2 hours and the modification temperature is 60°C. After modification, remove the excess coupling agent by centrifugal washing to ensure that the powder surface is clean and free of residue; Step 2: Mix the modified alumina nanopowder and stainless steel powder in a predetermined ratio, add a dispersant and a solvent to form a slurry; Step 3: Use an ultrasonic processor to mechanically stir the slurry during the ultrasonic treatment process, use a pH meter to monitor the pH value of the slurry in real time, and adjust the pH value to a range of 8-9 by automatically dropping a dilute acid or dilute alkali solution; Step 4: After the ultrasonic and mechanical stirring are completed, a predetermined amount of dispersant is added and stirring is continued for 30 minutes to allow the polymer dispersant to be fully adsorbed on the surface of the nanoparticles to form a stable dispersion system; Step 5: Introduce the slurry into the microfluidic chip, use the laminar flow effect and shear force to further refine the dispersion of the nanoparticles, collect the evenly dispersed slurry at the microchannel outlet, filter the evenly dispersed slurry, and obtain a slurry product of the nano-metal-ceramic composite material.

3. The method for forming an integrated metal structure according to claim 2, characterized in that: The preparation of the silver nanoparticle self-repairing coating comprises the following steps: Step 1: Select silver nanoparticles with self-repairing function; Step 2: Using silver nitrate as a precursor, reducing it in ethylene glycol to generate AgNPs, and adding polyvinyl pyrrolidone as a stabilizer; Step 3: The reaction temperature is controlled at 150°C, the reaction time is 2 hours, the molar ratio of polyvinyl pyrrolidone to silver nitrate is 1:1, and EG is used as a solvent and a reducing agent; Step 4: Disperse the nanoparticles in ethanol, add an appropriate amount of silane coupling agent, stir and react for 2 hours, and control the temperature at 60°C. After the reaction is completed, remove the excess coupling agent by centrifugal washing to ensure that the surface of the nanoparticles is clean and free of residue; Step 5: Add the modified self-healing nanoparticles to the epoxy resin base material in proportion, and use an ultrasonic processor to disperse the mixture. The ultrasonic frequency is 20 kHz, the power is 400 W, and the processing time is 30 minutes to ensure that the nanoparticles are evenly dispersed in the base material; Step 6: Adjust the viscosity of the slurry as needed, add diluent or thickener, and adjust it to a suitable range by dropping dilute acid or dilute alkali solution to obtain a self-repairing coating.

4. The integrated metal structural part of the operation panel prepared by the molding method of the integrated metal structural part according to claim 1, characterized in that: The integrated metal structure is the outer shell of the operating panel, the outer shell comprising a plate body (1) forming the main outline of the operating panel, the outer surface of the plate body (1) is provided with a plurality of functional grooves (2), the functional grooves (2) are correspondingly provided with a plurality of key reserved openings (3), and the plate body (1), the functional grooves (2) and the key reserved openings (3) are integrally injection molded.

5. The integrated metal structural part of the operation panel prepared by the molding method of the integrated metal structural part according to claim 4, characterized in that: The surfaces of the plate body (1), the functional slot (2) and the key reserved opening (3) are all provided with a self-repairing coating (4).

6. The method for forming an integrated metal structure according to claim 1, characterized in that: In the step 1, the particle size range of the stainless steel 316L powder is 10-30 μm, and the particle size range of the alumina nanopowder is 50-100 nm.

7. The forming method of the integrated metal structure and the integrated metal structure according to claim 1, characterized in that: In the step 2, the preheating temperature of the mold is 80-100° C., the sintering temperature of the heat treatment in the step 3 is 1200-1350° C., and the curing temperature in the step 6 is 150-200° C., and the curing time is 1-2 hours.

8. The method for forming an integrated metal structure according to claim 2, characterized in that: The dispersant is polyethylene glycol PEG, the solvent is ethanol, and the mass ratio of the dispersant to the total powder is 1:1.

5. The binder is polyvinyl alcohol PVA, which accounts for 2.5% of the total mass of the metal powder and the ceramic powder.

9. The method for forming an integrated metal structure according to claim 2, characterized in that: The ultrasonic processor was set to have an ultrasonic frequency of 20 kHz, a power of 400 W, and a processing time of 30 minutes.

10. The method for forming an integrated metal structure according to claim 2, characterized in that: The microchannel size of the microfluidic chip is 100 μm×100 μm, and the flow rate at the microchannel inlet is set to 0.5 mL / min.

Citation Information

Cited By

  • A molding agent, a metal powder injection molding feedstock, and a metal powder injection molding method.

    CN122665999A